The Primacy of Freedom in Rousseau's Discours sur les Sciences et les Arts as related to the Contrat Social and the Emile - Cassidy, Carla (My University, 1979)
The emphasis in the thesis is on demonstrating the absolute primacy of freedom (autonomy) in Rousseau's thought. The intention of the thesis is to suggest some of the problemmatic 'irreconcilables' inherent in any attempt to construct a political theory within the constraint of the primacy of freedom. This emphasis and intention is attempted through analysis of the concluding paragraphs of the Discours sur les Sciences et les Arts in relation to the Contrat Social and the Emile.
The actual thesis of the thesis is formulated to reflect the primacy of freedom in Rousseau's thought and is stated as follows: The concluding paragraphs of Rousseau's first Discoursedelineate a paradigm within the context of which Rousseau will later formulate his political projection, the Contrat Social, and his educational projection, the Emile. The terms 'paradigm' and 'projection' are used advisedly within the context of their centrality to modern thought. While recognizing that Rousseau did not use these terms in their evolved sense, the conceptual framework out of which they developed may be found in Rousseau's thought, particularly within the concluding paragraphs of the first Discourse.
Part I of the dissertation explores the paradigm outlined in the concluding paragraphs of the first Discourse. Specifically, Chapter I explores Rousseau's concept of freedom in relation to nature as manifest in the state of nature and human nature. Freedom is related to independence (vis-a-vis other men) and free-agency (vis-a-vis nature) and these two components form the basis for a typology of freedom that will be used throughout the thesis: natural freedom, misused freedom, and radical freedom. Chapter II examines Rousseau's historical perspective and his account in the first Discourse of the devolution of natural freedom into misused freedom (exercise of negative free-agency and loss of independence). Chapter III discusses Rousseau's concept of 'art' in order to further elucidate his concept of freedom and to reconcile Rousseau's praise of science in the concluding paragraphs with his attack on the arts and sciences earlier in the Discourse. Chapter IV contrasts the art of thinking', which Rousseau condemns, with the great science of Bacon, Newton and Descartes. Rousseau's designation of these men as the 'precepteurs du Genre-humain' , his description of the nature of their thought, and his demand that they be bound only by their own hopes, all demonstrate the extent to which Rousseau understood the relationship between freedom and projection that was to characterize modern thought. Chapter V identifies three types of virtue in Rousseau's thought (all of which are contrasted with the 'art of manners' attacked in the first Discourse): innocent virtue emanating from the primary goodness of man, political virtue based on the horizon of patriotism and religion, and autonomous virtue which is a type of self-legislation. Innocent virtue is simulated in Emile by the tutor and political virtue is established in the citizens by the legislator, whereas autonomous virtue characterizes those who are capable of exercising radical freedom.
In Part II, Chapter VI summarizes the paradigm outlined in Part I to serve as the basis for analyzing Rousseau's political and educational projections. Chapter VII explores the relationship between the legislator, who is identified as a 'precepteur du Genre-humain', that is, as one capable of exercising radical freedom, and the citizens of the general will state. This relationship is seen as a manifestation of the distinction Rousseau makes at the conclusion of the first Discourse between 'deux grands Peuples; que l'on savoit bien dire, et l'autre bien faire'. Chapter VIII parallels Chapter VII, by viewing the Emile as Rousseau's own projection within the context of the paradigm found in the first Discourse, particularly in the assignation of the tutor as a 'precepteur du Genre-humain' and in his relationship to Emile. Throughout my analysis, the emphasis is on demonstrating the primacy of freedom in all areas of Rousseau's thought: freedom for Rousseau is both the highest philosophic principle and the fundamental fact of human existence; it is the primacy of freedom that characterizes man's original condition, his fundamental desire and fundamental right; it is freedom that is the root and end of the just society.
In this emphasis on the primacy of freedom in Rousseau's thought, the thesis makes a signficant contribution to Rousseauan scholarship by providing a new perspective on the overall unity and consistency of Rousseau's thought, while, in a broader context, using Rousseau as the medium for exploring those irreconcilables which have become endemic to modernity's attempts to think together the exaltation of freedom (autonomy) as the highest good with the exigencies of political order.
Keywords: freedom; primacy; Rousseau; irreconsilables; political theory